(untitled) (Wageningen, Netherlands, 1994)
This book presents a complete and fully updated treatment of the timber species of South East Asia. Provides detailed information on 400 genera and 2900 timber yielding species, including detailed descriptions of trees and timbers
Keywords: Timber trees,Forests and forestry; Southeast Asia; Southeast Asia